2014
DOI: 10.4028/www.scientific.net/amm.490-491.1163
|View full text |Cite
|
Sign up to set email alerts
|

3D X-Y-T Space Path Planning for Autonomous Mobile Robots Considering Dynamic Constraints

Abstract: An autonomous mobile robot in a human living space should be able to not only realize collision-free motion but also give way to humans depending on the situation. Although various reactive obstacle avoidance methods have been proposed, it is difficult to achieve such motion. On the other hand, 3D X-Y-T space path planning, which takes into account the motion of both the robot and the human in a look-ahead time horizon, is effective. This paper proposes a real-time obstacle avoidance method for an autonomous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…We have confirmed that the proposed method can realize collision-free motion giving way to a human in the case where the human approaches slowly from immediately in front of the robot [24]. However, the relative position, velocity, and avoidance motion with respect to the robot varies from person to person.…”
Section: Introductionsupporting
confidence: 86%
“…We have confirmed that the proposed method can realize collision-free motion giving way to a human in the case where the human approaches slowly from immediately in front of the robot [24]. However, the relative position, velocity, and avoidance motion with respect to the robot varies from person to person.…”
Section: Introductionsupporting
confidence: 86%
“…Among them, the potential field and the evolutionary based methods are the most widely adopted approaches. These are significantly different from single vehicle path planning, where the grid based [87][88][89] or the road map based methods [90][91][92][93] are preferred.…”
Section: Discussion On Formation Path Planningmentioning
confidence: 99%
“…Анализ публикаций в таких научных журналах как Искусственній интеллект, Robotics and Autonomous Systems, Neural Networks, Expert Systems with Applications, Control Engineering Practice [4][5][6][7][8][9][10][11][12][13][14] показывает, что для решения задач управления сложными динамическими объектами в масштабе реального времени в условиях неопределенности и дефицита ресурсов используются методы принятия решений на основе систем искусственного интеллекта. В работе [4] выполнен обзор интеллектуальных алгоритмов планирования на основе технологии мягких вычислений: искусственных нейронных сетей (ИНС), нечеткой логики (НЛ), и генетических алгоритмов (ГА).…”
Section: анализ литературных данных и постановка проблемыunclassified